Perbandingan Metode Varmax Dan Prophet Dalam Peramalan Dan Analisis Harga Optimal Umroh Di Indonesia - Daziga, Ichwanda Brilliana; Gunardi, Gunardi (Seminar Nasional Official Statistics, 2024)
The optimal Umrah package price for organizers and consumers is a question. So far, determining package prices based on the facilities offered by the organizers has been done by calculating manually. For consumers to see the best price with the best facilities, of course they need benchmarks. This research aims to predict the price of Umrah packages using the Vector Autoregressive Moving Average With Exogenous Variables (VARMAX) statistical method compared with the Prophet method. Apart from endogenous factors, external variables are also added, namely the exchange rate. After that, the best model with the smallest values of Mean Absolute Error (MAE), Mean Square Error (MSE), and Mean Absolute Percentage Error (MAPE) is selected. It was found that the best model for predicting prices was the VARMAX (2,1) model with MAE, MAPE and MSE values of 2.2896, 7.5395 and 7.7435 respectively. It is hoped that the analysis of the results of forecasting prices for Umrah packages in Indonesia can be taken into consideration by both parties, namely Umrah organizers and consumers.